Grassy Narrows Blockade: Reworking Relationships between Anishnabe and Non-Indigenous Activists at the Grassroots - Wallace, Rick (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2010)
AbstractThe case example of Grassy Narrows argues that the localized experiences and discourses between Grassy Narrows First Nation ‘blockaders’ and non-Indigenous ‘activists’ reflected constrained and emancipatory practices of transforming various forms of asymmetrical power between them. Both a process and an outcome of negotiated understandings, collaboration and trust delineated by solidarity, the case of the Grassy Narrows First Nation (GNFN) blockade offered examples of grassroots practices for wider social change. In this case study, it was the negotiation from a marginalized position too often accorded the ontologies and epistemologies of one group—in this case, GNFN (Anishnabe peoples)—, and repositioning (privileging) it as the centre point of practice and leadership vis-à-vis another group (non-Indigenous activists). The case example asked what could be learned from a grassroots situation where differently situated parties have different privileges/status at the structural (macro) level but choose to attempt to renegotiate these at the local level. It suggested that transforming of larger social relations of power began at the local level through inverting/disabling unequal past practices and that in doing so, offered a counter point to established relations of power.